Three cases of COVID‐19 patients presenting with erythema. Issue 10 (17th August 2020) - Tamai, Masakazu; Maekawa, Aya; Goto, Noriko; Ge, Lindun; Nishida, Tsutomu; Iwahashi, Hiromi; Yokomi, Akinori
Abstract: Individuals infected with the novel coronavirus (Severe Acute Respiratory Syndrome Coronavirus 2 [SARS‐CoV‐2]) who develop coronavirus disease 2019 (COVID‐19) experience many symptoms; however, cutaneous manifestations are relatively rare. The authors encountered three patients with COVID‐19 who presented with erythema and suspected viral rash. In all cases, erythema appeared after the onset of the initial symptoms of COVID‐19. Erythema was considered to be caused by COVID‐19 and not a drug‐induced eruption because, in all cases, erythema was relieved merely by external medicine and oral antihistamines, without discontinuing the original medication. The authors' hospital accepted 69 COVID‐19 patients between 22 February 2020 and 31 May 2020 and, of these, three (4.3%) exhibited eruptions, and all cases presented erythema. Except for seven patients who exhibited positive nasopharyngeal swab tests for SARS‐CoV‐2 RNA but no symptoms, three (4.8%) of the remaining 62 patients exhibited erythema. Although various types of eruptions have been reported in patients with COVID‐19, erythema was the only type in our patients. Erythema in the three patients exhibited many similarities to that previously reported in COVID‐19 patients, particularly in the manner it appeared and disappeared. For these reasons, these three cases were considered typical examples of erythema in patients with COVID‐19. Considering previous studies and the three cases reported here, there is a high probability that SARS‐CoV‐2 can cause erythema.